Karakteristik Fisikokimia Dan Sensori Wheygurt Puree Ubi Jalar Ungu dan Stabilizer Gelatin - Muhammad Agung Aprialdi; Titi Rohmayanti; Widaningrum Widaningrum (Jurnal Ilmiah Pangan Halal, 2026)
Cheese is one of the most popular dairy products, known as a milk derivative produced by acidification using Lactobacillus bulgaricus through a coagulation process. In its production, milk with the addition of rennet enzyme undergoes curding, resulting in a solid fraction (cheese) and a by-product (whey). Whey can be utilized to produce wheygurt with the addition of stabilizers to increase viscosity and reduce syneresis. This study examined the formulation of wheygurt with the addition of purple sweet potato puree (15%, 30%, 45%) and the use of gelatin as a stabilizer. The experiment was conducted in the laboratory with two replications, referring to the Indonesian National Standard (SNI) for yogurt 2981:2009. The results showed that increasing the concentration of puree decreased fat content and total dissolved acids, but enhanced inhibitory activity. The highest protein content was obtained in the treatment with 45% purple sweet potato puree. Sensory evaluation indicated that the 45% puree formulation achieved the best results in terms of color, yogurt aroma, texture, and sour taste. Meanwhile, hedonic testing (overall preference) revealed that the 45% puree formula was more favored compared to other formulations.